Pengembangan Modul Proyek Penguatan Profil Pelajar Pancasila (P5) Pembuatan Arang Briket Dari Sampah Daun Sebagai Bahan Bakar Alternatif - Anggina, Viona Novi; Holiwarni, Betty; Haryati, Sri (Program Studi Pendidikan Kimia, FKIP, Universitas Riau, 2025)
This study aims to produce a P5 module for making charcoal briquettes from leaf waste as an alternative fuel that is valid according to the aspects of content feasibility, language, presentation, graphics and appearance. The type of research used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The data collection instrument used was a validation sheet given to 3 validators, a user response sheet to 2 teachers and 20 students. The results of the study obtained an average percentage score of the assessment of material expert and media expert validators of 96.35% and 95.83% with a valid category. The results of the trial to 2 teachers and students obtained an average percentage score of 93.23% and 93.08% with a very good category. Based on the results of the study, it can be concluded that the Pancasila student profile strengthening project module (P5) for making charcoal briquettes from leaf waste can be used in P5 activities.